THE CRITERIA OF PROCESS OF FORMATION OF VALUABLE BELIEF OF THE FUTURE MUSICIAN-TEACHER - Byelikova О.А. (Pedagogy of Higher and Secondary Education, 2007)
The problem of valuable belief of the future musicians-teachers is considered in the article. The criteria cof process of formation of valuable belief are defined there with the purpose of their effective usage in teaching and educational process.